If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7x^2)=69
We move all terms to the left:
(7x^2)-(69)=0
a = 7; b = 0; c = -69;
Δ = b2-4ac
Δ = 02-4·7·(-69)
Δ = 1932
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{1932}=\sqrt{4*483}=\sqrt{4}*\sqrt{483}=2\sqrt{483}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{483}}{2*7}=\frac{0-2\sqrt{483}}{14} =-\frac{2\sqrt{483}}{14} =-\frac{\sqrt{483}}{7} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{483}}{2*7}=\frac{0+2\sqrt{483}}{14} =\frac{2\sqrt{483}}{14} =\frac{\sqrt{483}}{7} $
| 9e+4=14+8e9e+4=14+8e | | 9=1-2s | | 2y-2=-2-4y | | 10=0.50(20)=b | | 7/2q=35 | | 9=6k | | 2(3x+12)=6x+12 | | F(4y)=-2•4y-3 | | 3(-1)-2y=0 | | 6(3r-5/2)+4=52 | | 5x(4x+2)-3x+2=-144 | | Y=(x+7)2=69 | | 6(3r-5)/2)+4=52 | | 6x2-24x=0 | | —x^2+16=0 | | -12-m=-3m+1-12m | | 3d+56=d+17 | | 2q+10-14q+60=21 | | y=0.75+4.87 | | −w20=−2.5 | | x÷2-3=2 | | 2w^2+9W=-9w | | 6x2-23x-4=0 | | 2a+5a-3=0 | | 14z^2+19z-3=0 | | 295.40=170+0.57x | | .50c+1.50c=206.50 | | 5/12-1/3x=5x/3 | | 2x+(-3)=7 | | 4x-9=6-6 | | 8h+9=11h | | 1/3+h=4 |